Modelling A Knowledge Base Using Object-Oriented Approach For Virtual Learning Environment - Mohd Yusof, Mohd Fairuz (2004)
The thesis describe the work of the research done to model a knowledge base. The knowledge base is one of the components of the Multimedia Knowledge Base E-Learning (MKBE-Learning) project which is still in progress( Ewe, H.T. et al., 2003).The thesis discusses the modelling of the knowledge base architecture using Object-Oriented Analysis and Design (OOAD)(Booch, G., 1999).